PLASTIC POLLUTION AS A THREAT TO HUMAN SECURITY: EXAMINING THE ISSUE AND PROPOSING SUSTAINABLE SOLUTIONS - Syed Zaheer Haider Jafri (International Journal of Contemporary Issues in Social Sciences, 2024)
Plastic pollution has emerged as a global crisis, posing significant threats to human security, environmental sustainability, and public health. This research paper aims to explore the multifaceted dimensions of plastic pollution and its profound implications on human security. By examining the sources, impacts, and socio-economic aspects of plastic pollution, the paper seeks to shed light on the urgency of addressing this issue. Furthermore, the paper proposes comprehensive and sustainable solutions to reduce plastic waste and mitigate the adverse effects on human security.